Social policy and social legislation A jurisprudential interface - Dr. Shefali Raizada, Prof. (International Journal of Engineering and Technology, 2018)
Principle of democracy as governance is for the people by the people and of the people. People are not the recipient of state framed policies and programs. Citizens are not only consumers, choosers or users, but active participants for making and shaping the policies.According to Duguit, â€œEssence of law is to serve and secure social solidarity, where individual has to perform obligations as a member of the communityâ€. Duguit says â€œeveryone has to perform his duties to the society which would help to develop cooperation and social solidarity.â€ Law and society are interrelated and interdependent. Changes in every social component leads to change in various aspects, right from the social institutions, customs, ideologies, human behavior and human interactions.Law is meant for nonprofessionals. The welfare of the society &humanity is the sole purpose of Indian constitution. To take care of interests, social security, social solidarity are the main aim of law. Sociological school of thought says that â€˜Law is social phenomenonâ€™. According to this school, essential characteristic of law should be to represent common interaction of men in social group. Treatment towards law should be as instrument of social control and social progress. The role of law and its functioning towards society is the basic philosophy of sociological jurisprudence.Thus, social progress is very much regulated by the degree of law. Law is like the steering to lead society in particular direction. Law may be the fulcrum to control society. Balance between law and society will certainly responsible for social progress.Â